Simulation and Evaluation of Acoustic Environments. Issue 1 (March 2014) - Vorländer, Michael
Humans experience their environment in various working, educational and living situations and in concert halls and opera houses. Whether the environment is considered acoustically appropriate or not depends on many factors. The research unit SEACEN is currently working on a coordinated effort to improve the complete signal chain from the numerical modelling, the data acquisition within numerical or real sound fields, the coding and transmission to the electro-acoustic reproduction by binaural technology or by sound field synthesis. A novel approach for the comparative evaluation of real and simulated environments will also enable the evaluation of the plausibility and/or the authenticity of virtual acoustic environments and a contribution to the development of better physical metrics to predict the qualities of concert halls and opera houses. These activities are relevant not only for concert hall acoustics but for acoustic spaces in general. The activities of SEACEN are summarized. The benefit from having these projects coordinated in a consortium is in the connection between all projects through perception studies and knowledge and data transfer between the groups. The commonly used factors in ISO 3382-like applications in classical room acoustics for concert hall design and consulting will be re-visited, and an extended parameter set will lead to progress in coding and reproduction of 3D sound fields in general. It is hoped that in the end room acoustics and audio engineering will benefit from this cooperation.